Using the Somatic, Auditory, Visual, and Intellectual (SAVI) Learning Model for Improving Geometry Ability in Early Childhood - Mutia Afnida; Winda Sherly Utami (JPUD - Jurnal Pendidikan Usia Dini, 2024)
One of the most important areas of mathematics education that must be developed from a young age is geometry. Various studies state that arithmetic, geometry, and measurement are three mathematical disciplines that must be prioritized in early childhood education. This research aims to determine the effect of the Somatic, Auditory, Visual, and Intellectual (SAVI) learning model on the geometric abilities of children aged 5-6 years. This research uses a pre-experimental experimental method with a one-group pretest-posttest design. The sample in this study was 18 children aged 5-6 years old Harapan Bunda Kindergarten Pancung Sol Pesisir Selatan. Data collection was obtained from observation and documentation, then the data was analyzed using paired sample tests. The results obtained in this research are that the SAVI model can improve the geometric abilities of children aged 5-6 years. This is known from the results of the paired sample t-test, which obtained a significance value of 0.000 < 0.05, which means Ho is rejected and Ha is accepted so that children's initial mathematical abilities, geometry, increase through the SAVI learning model. Children may become actively involved in their education with the help of the SAVI learning model, particularly when it comes to teaching them geometric forms. Because the teacher may utilize real items to aid in learning, children can recognize and retain the geometric forms around them as they grow older. Keywords: SAVI learning model, geometry ability, early childhood References: Alfiani, D. A. (2016). Penerapan Model Pembelajaran SAVI (Somatis, Auditori, Visual, Intelektual) Terhadap Hasil Belajar Aanak Usia Dini. Jurnal Pendidikan Anak, 2(1), 1-15. https://www.syekhnurjati.ac.id/jurnal/index.php/awlady/article/view/763 Amineh, R. J., & Asl, H. D. (2015). Review Of Constructivism And Social Constructivism. Journal of Social Sciences, Literature and Languages, 1(1), 9-16. Andrianti, R. Y., Irawati, R., & Sudin, A. (2016). Pengaruh Pendekatan SAVI (Somatic, Auditory, Visual, Intellectual) Dalam Meningkatkan Kemampuan Komunikasi Matematis Dan Motivasi Belajar Siswa Sekolah Dasar Pada Materi Pengolahan Data. Jurnal Pena Ilmiah, 1(1), 471-480. https://ejournal.upi.edu/index.php/penailmiah/article/view/2976 Birel, G. K., Deniz, D., & Onel, F. (2020). Analysis of primary school teachers’knowledge of geometry. International Electronic Journal of ElementaryEducation, 12(4), 303-309. Dewi, D. M. T., Masitoh, S., & Bachri, B. S. (2019). Improve Language And Cognitive Ability Through SAVI Learning Model With Lego Media For Preschool Child In Group A. Advances in Social Science, Education and Humanities Research, 212, 715-719. http://doi.org/10.2991/icei-18.2018.162 Elia, I., & Heuvel-panhuizen, M. V. D., & Gagatsis, A. (2018). Geometry Learning in the Early Years : Developing Understanding of Shapes and Space with a Focus on Visualization. 73–95. http://doi.org/10.1007/978-981-10-7153-9_5 Gejard, G., & Melander, H. (2018). Mathematizing in preschool: Children’sparticipation in geometrical discourse. European Early ChildhoodEducation Research Journal, 26(4), 495-511. Gilmore, J. H., Knickmeyer, R. C., & Gao, W. (2018). Imaging Structural And Functional Brain Development In Early Childhood. Nature Review: Neuroscience. 19, 123-137. Gohel, K. (2020). A Study of effectiveness of auditory learning style instructional strategy on science achievement with reference to study habit. Purakala (UGC Care Journal), 31(4), 412-420. Hardy, J. K., & Hemmeter, M. L. (2019). Systematic Instruction of Early Math Skill For Preschoolers At Risk For Math Delays. Topics in Early Childhood Special EducationI, 38(4), 234-247. https://doi.org/10.1177/0271121418792300 Hariawan, R., Nurul, U., Muhammad, H. A. Y., & Imron, A. (2019). Contributions Management of Parenting and Education Program to Strengthen The Service Three Early Childhood Education Center. International Education Studies. 12 (2). http://doi.org/10.5539/ies.v12n2p100 Hosain,M., & Wiest,L.R. (2013). Collaborative Middle School Geometry Through Blogs And Otherweb 2.0 Technologies. Journal of Computers in Mathematics and Science Teaching, 32(3), 337–352. https://eric.ed.gov/?id=EJ1006190 Hwang, W. Y., Hoang, A., & Tu, Y. (2019). Exploring Authentic Contexts With Ubiquitous Geometry To Facilitate Elementary School Students’ Geometry Learning. The Asia-Pacific Education Researcher, 29, 269-283. https://doi.org/10.1007/s40299-019-00476-y Hwang, W. Y., Liu, Y. F., Purba, S. W. D., & Zhang, Y. Y. (2018). Investigation On The Effects Of Measuring Authentic Contexts On Geometry Learning. IEEE Transactions on Learning Technologies, 12, 291-302. Ivrendi, A., Erol, A., & Atan, A. (2018). Developing a test for geometry andspatial perceptions of 5-6 year old. Kastamonu Education Journal, 26(6). Kencanawati, S. A. M. M., Sariyasa, S., & Hartawan, I. G. N. Y. (2020). Pengaruh penerapan model pembelajaran SAVI (Somatic, Auditory, Visual, Intellectual) terhadap kemampuan berpikir kreatif matematis. Pythagoras: Jurnal Pendidikan Matematika, 15(1), 13–23. https://doi.org/10.21831/pg.v15i1.33006 Lee, J. E. (2017). Preschool Teachers’ Pedagogical Content Knowledge In Mathematics. International Journal of Early Childhood. 49, 229-243. Meier, D. (2000). The Accelerated Learning Handbook A Creative Guide To Designing And Delivering Faster, More Effective Training Programs. United Kingdom: McGraw-Hill. Murti, E. D., Nasir, N., & Negara, H. S. (2019). Analisis Kemampuan Pemecahan Masalah Matematis : Dampak Model Pembelajaran SAVI ditinjau dari Kemandirian Belajar Matematis. Desimal: Jurnal Matematika, 2(2), 119–129.https://doi.org/10.24042/djm.v2i2.4072. National Research Council. (2009). Mathematics Learning In Early Childhood: Paths Toward Excellence And Equity.Washington, DC : National Academies Press. Ozcakir, B., Konca, A. S., & Arikan, N. (2019). Children’s Geometric Understanding Through Digital Activities: The Case Of Basic Geometric Shapes. International Journal of Progressive Education, 15(3), 108-122. Parks, A. N. (2015). Exploring Mathematics Through Play In The Early Childhood Classroom. Teachers College Press. Partini, K. E., Wirya, I. N., & Ujianti, P. R. (2017). Pengaruh Metode Proyek Terhadap Kemampuan Mengenal Bentuk Geometri Pada Kelompok B Gugus I Singaraja Semester I. e-Journal Pendidikan Anak Usia Dini: Universitas Pendidikan Ganesha, 5(2), 210-219. https://ejournal.undiksha.ac.id/index.php/JJPAUD/article/view/12606/12967 Pauli, C., & Reusser, K. (2015). Co-constructivism in educational theory andpractice. International Encyclopedia of the Social and Behavioral Sciences.(Second Edition). 913-917 Raiyn, J. (2016). The Role of Visual Learning in Improving Students’ High-Order Thinking Skills. Journal of Education and Practice, 7(24), 115-121. http://iiste.org/Journals/index.php/JEP/article/view/32607/33498. Reeve, R. A. (2019). Mathematical Learning And Its Difficulties In Australia. International Handbook of Mathematical Learning Difficulties, 253–264. http://doi.org/10.1007/978-3-319-97148-3 _16 Rohman, N., Rustono., & Rifa’i, A. (2016). Cooperative Learning Model To Increasing Mathematical Concept For Early Childhood. Indonesian Journal of Early Childhood Education Studies, 5(1), 54-58. https://doi.org/10.15294/ijeces.v5i1.11277 Sahara, R., Mardiyana., & Saputro, D. R. S. (2018). Discovery Learning With SAVI Approach In Geometry Learning. Journal of Physics: Conference Series, 1013, 1-5. https://iopscience.iop.org/article/10.1088/1742-6596/1013/1/012125 Sarnoko., Ruminiarti., & Setyosari, P. (2016). Penerapan Pendekatan SAVI Berbantuan Video Pembelajaran Untuk Meningkatkan Aktivitas Dan Hasil Belajar IPS Siswa Kelas IV SDN I Sanan Girimarto Wonogiri. Jurnal Pendidikan, 1(7), 1235-1241. http://journal.um.ac.id/index.php/jptpp/article/view/6524 Selmi, A. M., Gallagher, R. J., & More-Flores, E. R. (2014). Early Childhood Curriculum For All Learners: Integrating Play And Literacy Activities. SAGE Publications. Septia, P., Pandra, V., & Mandasari, N. (2023). Penerapan Model Pembelajaran SAVI Dalam Pembelajaran Bangun Ruang Untuk Mengukur Hasil Belajar Matematika, Journal of Elemantary School (JOES), 6(2), 468-476. https://doi.org/10.31539/joes.v6i2.6661 Shoimin, A. (2014). 68 Model Pembelajaran Inovatif Dalam Kurikulum 2013. Yogyakarta: Ar-ruzz Media. Sulaksana, Y. T., Margunayasa, I. G., & Wibawa, I. M. C. (2018). Pengaruh ModelPembelajaran SAVI (Somatic Auditory Visualization Intellectualy) Berbantuan LKS terhadap Hasil Belajar IPA. Jurnal Pedaagogi Dan Pembelajaran, 1(3).http://dx.doi.org/10.23887/jisd.v3i3.18895. Thersia, V., Arifuddin, M., & Misbah. (2019). Meningkatkan kemampuanpemecahan masalah melalui pendekatan somatis auditori visual intelektual(SAVI) dengan model pengajaran langsung. Berkala Ilmiah PendidikanFisika, 7(1), 19-27. Tutak, F. A., & Adams, T. L. (2015). A study of geometry content knowledge ofelementary preservice teachers. International Electronic Journal ofElementary Education, 7(3), 301-318. Utami, W. S., & Sri, I. H. (2023). Pengembangan Model Stimulasi Geometri Berbasis Pendekatan SAVI (Somatic, Auditory, Visual, Intellectual) untuk Anak Usia Dini. Jurnal PG-PAUD Trunojoyo: Jurnal Pendidikan dan Pembelajaran Anak Usia Dini, 10(1), 25-36. https://doi.org/10.21107/pgpaudtrunojoyo.v10i1.18879 Wijaya, I. K. P., Bayu, G. W., & Sumantri, M. (2021). Model Pembelajaran Somatis, Auditory, Visualization, Intellectualy (SAVI) Berbantuan Icebreaker Terhadap Hasil Belajar IPA Siswa. Jurnal Ilmiah Pendiddikan Profesi Guru, 4(1), 54-60. http://dx.doi.org/10.23887/jippg.v4i1 Yudiari, M. M., Parmiti, D. P., & Sudana, D. N. (2015). Pengaruh Model Pembelajaran SAVI Berbantuan Media Mind Mapping Terhadap Hasil Belajar IPA Siswa Kelas V. MIMBAR PGSD Undiksha, 3(1). http://dx.doi.org/10.23887/jjpgsd.v3i1.5683. Yuliana, D., & Sisma, R. U. A. (2019). Penerapan Model Pembelajaran Savi (Somatis,Auditori, Visual, Dan Intelektual) Untuk Meningkatkan Minat Dan Hasil BelajarPeserta Didik. Jurnal Pendidikan Dan Kewirausahaan, 7(1).https://doi.org/10.47668/pkwu.v7i1.19.